Peak-to-Peak Output Current Ripple Analysis in Multiphase and Multilevel Inverters - Loncarski, Jelena (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2014)
The book introduces an original and effective method for the analysis of peak-to-peak output current ripple amplitude in three-phase two-level inverters. It shows that the method can be extended to both multiphase inverters, with particular emphasis on five-phase and seven-phase inverters, and multilevel ones, with particular emphasis on three-level inverters, and provides, therefore, a comparison among different number of output phases and voltage levels. The work reported on here represents the first detailed analysis of the peak-to-peak output current ripple. It makes an important step toward future developments in the field of high-power generation, and in grid-connected and motor-load systems.